Analysis of Factors Driving Customer Satisfaction in Murabahah Financing at BMT Tanjung Paiton Probolinggo - Yuniati, Sri (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
This study aims to describe the results of the analysis of the factors that encourage customer satisfaction in murabahah financing at BMT Tanjung Paiton Probolinggo. To facilitate the research process, this research process uses a qualitative-descriptive approach. The research stages consist of the orientation stage or pre-field stage, the field activity stage and the data analysis stage. Data collection techniques using interviews, observation and documentation. Sources of data used are primary and secondary data sources. The data analysis uses data reduction, data display and conclusion drawing/verification. The data validity technique uses the credibility test, transferability test, dependability test, and comfirmability test. The results showed that BMT Tanjung Paiton Probolinggo was very concerned about customer satisfaction. Customer satisfaction in financing at BMT Tanjung Paiton Probolinggo has several factors. Among these factors, namely: 1) the procedures and services do not complicate the customers of BMT Tanjung Paiton Probolinggo; 2) if there is a problem between BMT Tanjung Paiton and its customers, then both use the family system; 3) the language of instruction uses the Madurese language, so it is comfortable to communicate; 4) ujroh BMT Tanjung Paiton Probolinggo is only 1.5% affordable; 5) BMT Tanjung Paiton Probolinggo does not impose a fine if the installment payment is late; and 5) the contract used in the financing process at BMT Tanjung Paiton Probolinggo uses a rohn contract.